The high-osmolarity glycerol (HOG) pathway in Candida auris - Hajar Yaakoub; Vincent Courdavault; Nicolas Papon (mBio)
ABSTRACT The emerging fungal pathogen Candida auris is known for its strong skin tropism and resilience against antifungal and disinfection treatment, posing a significant challenge for healthcare units. Although efforts to identify the effectors of its unique pathogenic behavior have been insightful, the role of the high-osmolarity glycerol (HOG) pathway in this context remains unexplored. The study by Shivarathri and co-workers (R. Shivarathri, M. Chauhan, A. Datta, D. Das et al., mBio 15:e02748-24, 2024, https://doi.org/10.1128/mbio.02748-24) sought to address this gap. This report indeed advances our understanding of the critical role of the HOG pathway in C. auris pathogenicity by emphasizing its involvement in skin colonization, biofilm formation, and evasion of phagocyte attack.